Citrus aurantiifolia and citrus microcarpa fruit peels waste as eco-friendly natural coagulants. Issue 1 (April 2020) - Dollah, Z; Sahat, N A; Hamzah, N; Musir, A A; Ramli, R
Abstract: Turbidity is one of the importance of physical water quality parameter in the water treatment process. Aluminum sulfate (alum) and ferric chloride are the most widely groups of chemical coagulant and have been extensively used to remove turbidity. However, there are several flaws relates to the environmental issue and impose health risk to the consumer. Fruit peel waste as a natural coagulant is one of the alternative techniques in minimizing the usage of chemical coagulant in water treatment. This research focused on a combination of ratio 60:40 and 80:20 of citrus microcarpa peels and citrus aurantiifolia peels to act as a natural coagulant for turbidity removal. Furthermore, the effect of mixing duration is determined to establish the optimum mixing duration for the highest turbidity removal. Standard practice using jar test were performed in synthetic turbid water using kaolin. The highest turbidity removal occurred at optimum ratio of 80:20 with 77.6% efficiency removal where the optimum mixing duration was found to be at 120 rpm of rapid mixing at 3 minutes, 50 rpm of slow mixing at 20 minutes and 60 minutes of settling time. The study demonstrated that combination of citrus aurantiifolia peels and citrus microcarpa peels have the potential to be used as natural coagulant for a future alternative in water treatment.